2011
DOI: 10.1186/1476-511x-10-80
|View full text |Cite
|
Sign up to set email alerts
|

Oral P. gingivalis infection alters the vascular reactivity in healthy and spontaneously atherosclerotic mice

Abstract: BackgroundConsidering that recent studies have demonstrated endothelial dysfunction in subjects with periodontitis and that there is no information about vascular function in coexistence of periodontitis and atherosclerosis, we assessed the impact of oral inoculation with the periodontal pathogen Porphyromonas gingivalis on vascular reactivity in healthy and hypercholesterolemic apolipoprotein E-deficient (ApoE) mice. In vitro preparations of mesenteric arteriolar bed were used to determine the vascular respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 41 publications
0
20
0
1
Order By: Relevance
“…Moreover, several independent studies have detected P. gingivalis DNA or retrieved live bacteria from human aortic aneurysms, aortic thrombi, atheromas, and atherosclerotic plaque specimens [1], [2], [7][15]. Experimental infection with different strains of P. gingivalis have shown that the bacterium can promote varying degrees of cardiovascular disease including endothelial dysfunction [16], vascular smooth muscle proliferation [17], [18], aortic aneurysm [19][21], and atherosclerosis [22][27]. Although not specific to P. gingivalis , intensive periodontal therapy has been shown to improve endothelial function in the long-term in patients with periodontal disease [28].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, several independent studies have detected P. gingivalis DNA or retrieved live bacteria from human aortic aneurysms, aortic thrombi, atheromas, and atherosclerotic plaque specimens [1], [2], [7][15]. Experimental infection with different strains of P. gingivalis have shown that the bacterium can promote varying degrees of cardiovascular disease including endothelial dysfunction [16], vascular smooth muscle proliferation [17], [18], aortic aneurysm [19][21], and atherosclerosis [22][27]. Although not specific to P. gingivalis , intensive periodontal therapy has been shown to improve endothelial function in the long-term in patients with periodontal disease [28].…”
Section: Introductionmentioning
confidence: 99%
“…More recent work suggests that other virulence factors of P. gingivalis may be equally important for the progression of atherosclerosis since the fimbriae-deficient strain W83 [41] also promotes atherosclerosis in ApoE deficient mice [26]. In contrast, strain 33277, which is closely related to strain 381 [42] does not accelerate atherosclerosis in ApoE deficient mice [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2003; Amar et al. , 2009; Pereira et al , 2011). Various theories have been proposed to explain this link.…”
Section: Introductionmentioning
confidence: 99%
“…4 It was also demonstrated that a P. gingivalis infection causes an increased vasoconstrictor response to phenylephrine both in mice with spontaneous atherosclerosis and in healthy mice. 35 However, the virulence mechanisms are different for various P. gingivalis strains and a detailed examination of these processes needs to be performed. 32 In this study, the assessment of the presence of P. gingivalis DNA in cardiac valves in relation to its presence in periodontal pockets was performed.…”
mentioning
confidence: 99%